Development of Physics HOTS Assessment Instruments in High School: A Comprehensive Literature Review - Bhakti, Yoga Budi; Arthur, Riyan; Supriyati, Yetti (JIPF (Jurnal Ilmu Pendidikan Fisika), 2025)
This study aims to identify strategies for developing HOTS assessment instruments in high school physics subjects. The research employs bibliometric methods and qualitative approach to analyze various journals published between 2019 and 2023. The analysis results indicate that the development of HOTS instruments is driven by the need for 21st-century skills and is supported by findings from international surveys such as PISA and TIMSS. The most commonly developed assessment forms include test questions in the form of multiple choice, multiple choice with reasoning, and essays. These questions are designed with HOTS characteristics in mind, including HOTS indicators, operational verbs, physics problem contexts, stimuli, and Bloom's taxonomy. Physics topics that are frequently developed include subjects such as temperature and heat, harmonic vibrations, sound and light waves, thermodynamics, as well as static and dynamic fluids. Commonly used research methods for this development include Borg and Gall's R&D method, the 4D method, qualitative descriptive methods, and the ADDIE method. HOTS instrument undergoes a series of feasibility tests and analyses, including validity testing by validators, statistical validity tests, reliability tests, difficulty level tests, discrimination index tests, Rasch model analysis, analysis using the Alpha Cronbach formula, and distractor analysis. The findings of this study provide valuable insights for developing valid, reliable, and relevant HOTS assessment instruments that meet the needs of high school physics education.